Malaysian Traditional Game (Tradesa Melayu) Learning Application - Zainurin, Muhammad Zuhairi; Burhanudin, Muhammad Nukman Hafiz; Salman, Muhammad Iqbal; Ibrahim, Zuraida (Multidisciplinary Applied Research and Innovation, 2024)
Games that have been played in a culture or society for many years are referred to as traditional games. They are a vital piece of cultural heritage that must be protected. This study aims to create applications for Malaysian traditional games that will empower them within the community. In addition, the method used to complete this project is the ADDIE model which has 5 stages namely Analyze, Design, Develop, Implement, Evaluate. This is a recommended core component for all application development projects. Furthermore, there are a variety of reasons why modern society has forgotten about traditional games. This is because children in Asia between the ages of 3 and 8 are more interested in using technology than playing traditional games with their friends. Unfortunately, traditional games provide numerous benefits such as sharpening children's brain development, generating empathy, developing social awareness, and developing creativity. As a solution, developing applications related to traditional games in Malaysia can provide knowledge to the community about traditional games because it is part of the nation's heritage and culture that must be preserved and celebrated so that it does not disappear due to modernity and the presence of today's technology. Findings show that this traditional game is very important to preserve values, traditions, and cultural identity. In conclusion, we hope that the Traditional Games Application (TraDesa Melayu) can help children get interested and better understand the traditional games of our culture.